How does cleaner energy transition influence standard of living and natural resources conservation? A study of households' perceptions in rural Odisha, India. (15th January 2021) - Swain, Swadhina Shikha; Mishra, Pulak
Abstract: While importance of cleaner cooking fuels for improving quality of life and facilitating social inclusion and ecological sustainability is well-recognized, success of the initiative depends on beneficiaries' perceptions about the potential benefits. Here, we examine how the beneficiaries perceive about the benefits of the Pradhan Mantri Ujjwala Yojana (PMUY), an initiative of the Government of India, which aims at providing subsidised connections of liquefied petroleum gas (LPG) to the poor households of the country. Perceptions are examined in respect of changes in standard of living and natural resource conservation. Based on primary data and information collected from five villages of the Puri district of Odisha, it is found that beneficiaries perceive only marginal or no change in standard of living after LPG connection in India. Further, the estimated limited dependent variable models show that such perceptions depend on household heads' education, subsidy on LPG and changes in firewood use. However, occupation or household income does not have any significant impact on perceptions. Efforts should, therefore, be made towards raising awareness of beneficiaries, making LPG cheaper and restricting firewood use for changing households' perceptions about the benefits of LPG toward greater success of the PMUY. Highlights: Cleaner fuels improve quality of life and facilitate sustainability. Success of initiatives depend on perceptions. Education, subsidy and firewood use influence perceptions. There is need for greater awareness, cheaper LPG and restriction on firewood.